Abandoned housing projects in Peninsular Malaysia: Problem and suggestions - Md Dahlan, Nuarrual Hilal (2010)
Housing industry is one of the important agendas in Malaysia since Independence day. It is also one of basic needs and rights of mankind. Since then, it has been placed in the list of the top government's priorities in the Malaysia's Plans. After Independence, one of the most important objectives of the government is to restructure the society and eradicate poverty, through the means of the various Malaysia Plans, the pre-emptive New Economic Policy (NEP) and the National Development Policy (NDP) adopted by the government. One of the approaches contained in these programmes and means, is to provide sufficient and suitable housing accommodation to its citizens. Initially, after Independence, the duty to provide housing for the citizens of Malaya (the then Peninsular Malaysia) was resumed by the Malaysian government itself; following the step of the British-led government before it. However, due to the insufficient funds on part of the government and there were upsurge in demand for housing democracy and ownership, this noble task had also been given to private developers, for them to provide and construct housing accommodation, subject to the rules and regulations imposed by the government. Be that as it may, although housing industry has served as the development, economic and social catalyst and has brought many benefits to the nation, one of the spill-over problems which it carries is the problem of abandoned housing projects. This problem has become a nightmare to the government and especially to the purchasers involved Based on initial researches there are various kinds of reasons leading to such a catastrophe. It is thought that, legally speaking, this problem might have been and it is evident, due to certain legal problems. Thus, on this footing, this paper, will look into the legal provisions available that concern the abandoned housing projects and will identify the related legal problems. Following this, the author will suggest certain legal approaches to overcome and avoid these problems from recurring in the future as well as the legal approaches to ensure the success of any rehabilitation.